An Investigation On Apathy And Altruism In Urbam Society Of Iran - S. Kalantary; M. Adibi; R. Rabbani; S. Ahmadi (روانشناسی بالینی و شخصیت, 2007)
Since 1960's a vast amount of research is conducted on altrusim and apathy in social relationships. But doing such studies haven’t been paid due attention to in Iran. The purpose of this research is primarily to determine the rate of altrusim and apathy in urban society of Iran and also to investigate the relationship between altruism – apathy, empathy,social responsibility and cost-reward analysis. The method employed in this study is causal- comparative method which is done in two stages. In the first stage, that was conducted for determining of altruist and apathetic groups, researcher confederates referred to different houses and created a spurious emergency situation. The subjects were classified in altruist or apathetic groups on the basis of their reactions to this emergency situation. In second stage, questioners referred to the same subjects and collected required informations.Sampling unit was houses and 384 houses were selected in different regions of Shiraz by means of random multistage method. Measurment tool was a researcher - made questionnaire including 39 questions with likert scale of which 13 questions were for the measurment of empathy, 16 responsibility and 10 questions for the measurment of material cost– reward analysis. The validity of the measurment tool was determined by Content validity and the reliability was measured by Cronbach alpha in which the alpha coefficient for these three factors was .68 to.82 and for the total questionnaire was .75. The findings show that during occurrence emergency situations, rate of altruism is 75.3 and rate of apathy is 24.7. Furthermor, altruist group in comparison with apathetic group has more empathy, more responsibility and less material cost– reward analysis. The research findings, compared with previous studies results, also show that we can increase altruism and decrease apathy by means of raising empathy and responsibility and the reduction of material cost- reward analysis among citizens.